MOTIVASI MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU DALAM PENYELESAIAN SKRIPSI BERDASARKAN KEMAMPUAN AKADEMIS DAN EFIKASI DIRI - Anggriani, Vivi; Abd. Rasyid Syamsuri; Mida Aprilina Tarigan, Mida Aprilina Tarigan (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
The purpose of this study is to analyze academic ability and self-efficacy influencing student motivation to complete a thesis at the Faculty of Economics and Business, Riau University. This study employs quantitative methods. The population consists of all students in the class of 2017–2019 at the University of Riau's Faculty of Economics and Business; a total of 808 individuals were selected from this university's student database. In this study, 100 respondents were chosen as samples, based on sample calculations performed using the Slovin technique. Data is gathered by observation and documentation, as well as by using a Likert scale in the questionnaire. Techniques for data analysis make use of tests for validity, reliability, and traditional assumptions. The data analysis process made use of multiple linear regression using SPSS (Statistical Product Software Solution) software. Studies reveal that academic aptitude has a favorable and considerable impact on students' motivation. Self-efficacy has a strong and positive impact on students' motivation. Academic aptitude and self-efficacy at the Faculty of Economics and Business, Riau University, have an impact on students' motivation to finish a thesis.